The occurrence of abnormal body weight values and selected eating habits and physical activity of nurses - Waksmańska, Wioletta; Woś, Halina; Bobiński, Rafał (Journal of Medical Science, 2018)
Aim. The aim of the research was to analyze the incidence of abnormal body weight values and to assess eating habits and physical activity of nurses.Material and Methods. The studies involved all first‑year nursing students of the second degree daily studies, working as a nurse. The women’s eating habits were analyzed based the diet. The questionnaire allowed the researchers to determine daily consumption of each particular dietary component (proteins, carbohydrates, fats, fatty acids, vitamins) as well as the women’s calorie consumption.Results. The analysis showed that the group of underweight participants was comprised of 5 students (group I), the group of participants with normal body weight — of 43 students (group II), and the group of participants with excessive body weight — of 10 students (group III). Group II students spent the longest time on (moderate and intense) physical activity (on average 378 minutes/week), whereas group III students — the shortest (on average 203 minutes/week). While analyzing the average protein intake, it was found that all groups exceeded its daily requirement. The intake of sodium and cholesterol was exceeded more than twice of the recommended amount. A very low intake of vitamin D — covering from 40 to 48% of the daily requirement — was observed in all groups.Conclusions. Despite the fact that the nurses’ diet includes all nutrients necessary for the body, it is not properly balanced which obliges to raising awareness of types of consumed food.